2013
DOI: 10.1089/brain.2013.0166
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Effects of a Novel on Connectivity in the Brain

Abstract: We sought to determine whether reading a novel causes measurable changes in resting-state connectivity of the brain and how long these changes persist. Incorporating a within-subjects design, participants received restingstate functional magnetic resonance imaging scans on 19 consecutive days. First, baseline resting state data for a ''washin'' period were taken for each participant for 5 days. For the next 9 days, participants read 1/9th of a novel during the evening and resting-state data were taken the next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 31 publications
2
45
0
8
Order By: Relevance
“…Studies in the related literature demonstrated reading books enhances the connection between the parts of the brain (Berns, Blaine, Prietula, & Pye, 2013;Howard, 2013). Improved connection between the parts of the brain can allow learners to make efficient deductions (Howard, 2013).In support of this condition, Bloom (2012) reported the capacity to understand what is read allows for learning despite the changes in quality of teaching.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the related literature demonstrated reading books enhances the connection between the parts of the brain (Berns, Blaine, Prietula, & Pye, 2013;Howard, 2013). Improved connection between the parts of the brain can allow learners to make efficient deductions (Howard, 2013).In support of this condition, Bloom (2012) reported the capacity to understand what is read allows for learning despite the changes in quality of teaching.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Araştırmalar kitap okumanın beyindeki bölgeler arasındaki bağlantıyı artırdığını göstermiştir (Berns, Blaine, Prietula, & Pye, 2013;Howard, 2013). Bölgeler arasındaki bağlantının artmasıyla öğrenenlerin etkili çıkarımlarda bulunması sağlanabilir (Howard, 2013).…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Kompleksnost književnih djela, njihova moć da opčine čitatelja, da ga angažiraju na svim poljima -misaono, emotivno, kognitivno, pa i tjelesno -poticala je znanstvenike različitih područja da se bave njihovim nastankom. Najnovija istraživanja u području neuroznanosti pokazuju da čitanje može izazvati stvarne promjene u mozgu, da je te promjene moguće mjeriti, kao i da se, osim do sada poznatog uživljavanja u svijet romana ili lika, tijekom čitanja nešto događa i na biološkoj razini (Berns, 2013). Zbog toga ne iznenađuje što je i znanstvenike širom svijeta, posebno u vremenu u kojem je tehnološki moguće mjeriti utjecaje različitih činitelja, pa i čitanja, nastavila zaokupljati moć stvaratelja teksta i teksta samog.…”
Section: Uvod -Kreativno Pisanjeunclassified
“…All the more so that the latest research in the field of neuroscience shows that reading can cause actual changes in the brain that can be measured, and that, besides the already known immersion in the world of the novel or character, while reading, something happens at the biological level as well (Berns, 2013). It is not surprising that the scientists around the world, especially at a time when the technological measuring of effects of various factors is possible, notwithstanding the effect of reading, are continually occupied by the power of text creator and the text itself.…”
mentioning
confidence: 99%
“…Regular recreational reading is a highly beneficial practice, as it is associated with significant gains across a range of literacy outcomes [22][23][24]. Regular reading may also offer protection against cognitive decline [25,26] and foster empathy [27][28][29].…”
Section: Why Does Adolescent Preference Matter?mentioning
confidence: 99%